Aussies run, ride and workout at home during COVID-19`s shutdown of sport (Sport AUS, 2020)
With organised sport on hold due to COVID-19, Australians turned to running, riding, and yoga to stay active and socially connected according to Sport Australia`s latest AusPlay survey results that identify sport and physical activity habits across the country.